Cutting Tools
By imparting high compression residual stress on the fork surface of the titanium alloy cutting tool and controlling the hard phase structure, the problem of tools being susceptible to welding and wear in titanium alloy processing is solved, and the tool's high wear resistance and life extension is achieved.
Patent Information
- Application Number
- CN202180019577.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-26
- Filing Date
- 2021-04-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-04-07
AI Technical Summary
During the processing process, titanium alloys are easily welded to the cutting edge of the cutting tool due to high reactivity, resulting in cracking or reaction wear, and the prior art is difficult to effectively improve the tool life.
A cemented carbide cutting tool consisting of the first hard phase composed of WC particles and a bonding phase containing Co and Ni is used, and a compression residual stress of 1.0 GPa or more is imparted to the forefing surface of the tool to control the thickness and particle size ratio of the surface layer to improve the wear resistance of the tool.
By imparting sufficient compression residual stress and controlling the structure of the hard phase, the wear resistance of the cutting tool to titanium alloy is significantly improved, the life of the tool is extended, and the excellent wear resistance is shown in particular under high-speed cutting conditions.
Smart Images

Figure CN115243814B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a cutting tool. This application claims priority based on Japanese Patent Application No. 2020-091490 filed on May 26, 2020. All the contents described in the Japanese Patent Application are incorporated herein by reference. Background Art
[0002] In recent years, titanium alloys have been widely used in various applications, including aircraft parts, and the demand for their processing is also increasing. Titanium alloys have high properties as structural materials, but are difficult to process, especially wear and chipping caused by high temperatures. Although many attempts have been made to improve the tool life by controlling the surface of cemented carbide tools, they have not yet reached a level that fully meets the demand for titanium alloy processing.
[0003] For example, Patent Document 1 (Japanese Patent Publication No. 2003-1505) discloses a technology relating to the following tool materials: a tool material in which performance is improved by imparting high compressive stress to WC that is not a titanium alloy object but exists in the surface layer of cemented carbide, and a tool material in which cracking caused by welding with titanium alloy is suppressed by burying oxides in the surface.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-1505 Summary of the invention
[0007] A cutting tool according to one embodiment of the present disclosure is composed of a cemented carbide including a first hard phase and a binder phase.
[0008] The first hard phase is composed of WC particles.
[0009] The bonding phase includes at least one element selected from the group consisting of Co and Ni.
[0010] The cutting tool includes a main body portion and a surface layer portion provided on a surface of the main body portion.
[0011] A compressive residual stress of 1.0 GPa or more is applied to the first hard phase on a surface of a flat surface portion of the rake face of the cutting tool.
[0012] The thickness of the surface layer portion is equal to or less than an average grain size of the first hard phase on the surface of the flat surface portion of the rake face.
[0013] A ratio (B / A) of an average grain size (B) of the first hard phase on the surface of the flat surface portion of the rake face to an average grain size (A) of the first hard phase in the cross section of the body portion is 0.7 or more and less than 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] [ Figure 1 ] Figure 1 It is a schematic cross-sectional view of a cutting tool according to an embodiment.
[0015] [ Figure 2 ] Figure 2 This is a conceptual diagram for explaining the surface layer portion of the cutting tool according to the embodiment.
[0016] [ Figure 3 ] Figure 3 This is an enlarged cross-sectional view of a conventional cutting tool.
[0017] [ Figure 4 ] Figure 4 This is an enlarged cross-sectional view of other traditional cutting tools.
[0018] [ Figure 5 ] Figure 5 This is an example of a SEM photograph of the surface of a cutting tool (the surface of the flat surface portion of the rake face).
[0019] [ Figure 6 ] Figure 6 This is a SEM photograph of the surface of the cutting tool of Example 1.
[0020] [ Figure 7 ] Figure 7 This is a SEM photograph of the surface of the cutting tool of Comparative Example 101. DETAILED DESCRIPTION
[0021] [Problems to be Solved by the Present Disclosure]
[0022] Titanium alloys are easily welded to the cutting edge of a cutting tool due to their high reactivity, and repeated formation and peeling of the weld easily cause chipping or reactive wear of the tool cutting edge.
[0023] Since the shape of the cutting edge of the welding tool and the state of the surface are greatly affected by the welding, attempts have been made to control the surface composition and structure of the cutting tool in order to reduce the welding itself or improve the tolerance to cracking. However, in the processing of titanium alloys, the coating technology of the commonly used cutting tools is sometimes difficult to play an effective role, so it is necessary to further improve the tool life that meets market requirements.
[0024] In particular, in cutting under high-speed conditions, which has been increasingly in demand in recent years, the temperature of the interface between the tool and the workpiece tends to rise, and the expansion of damage to the cutting tool due to reactive wear has become a major problem.
[0025] It should be noted that the formation of the surface layer 13 having a predetermined thickness in the cutting tool 1 (see Figure 3 and Figure 4 ) may lead to a reduction in properties that are in a trade-off relationship with the properties to be improved (wear resistance), such as insufficient toughness when the hardness is increased. Therefore, it is not desirable to improve the wear resistance of the titanium alloy by forming a surface layer 13 having a predetermined thickness.
[0026] Therefore, an object of the present disclosure is to provide a cutting tool having high wear resistance to titanium alloys.
[0027] [Effects of the present disclosure]
[0028] According to the above, a cutting tool having high wear resistance to titanium alloy can be provided.
[0029] [Description of Embodiments of the Present Disclosure]
[0030] First, embodiments of the present disclosure will be listed and described.
[0031] It should be noted that in this specification, the expression in the form of "A to B" refers to the upper and lower limits of the range (i.e., greater than A and less than B). When no unit is recorded for A and only the unit is recorded for B, the unit of A is the same as the unit of B.
[0032] [1] A cutting tool according to one embodiment of the present disclosure is composed of a cemented carbide including a first hard phase and a binder phase.
[0033] The first hard phase is composed of WC particles.
[0034] The bonding phase includes at least one element selected from the group consisting of Co and Ni.
[0035] The cutting tool includes a main body portion and a surface layer portion provided on a surface of the main body portion.
[0036] A compressive residual stress of 1.0 GPa or more is applied to the first hard phase on a surface of a flat surface portion of the rake face of the cutting tool.
[0037] The thickness of the surface layer portion is equal to or less than an average grain size of the first hard phase on the surface of the flat surface portion of the rake face.
[0038] A ratio (B / A) of an average grain size (B) of the first hard phase on the surface of the flat surface portion of the rake face to an average grain size (A) of the first hard phase in the cross section of the body portion is 0.7 or more and less than 1.
[0039] In the present disclosure, since sufficient compressive residual stress is imparted to the surface (front face) of the cutting tool and the crushing of the first hard phase (WC particles) is suppressed, the wear resistance of the cutting tool can be improved. As a result, the cutting tool has high wear resistance to titanium alloys. Therefore, when used for cutting titanium alloys, etc., the life of the cutting tool can be extended.
[0040] [2] The cemented carbide preferably further includes a second hard phase. The second hard phase is composed of a compound of at least one element selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table and at least one element selected from the group consisting of C, N, O and B, or a solid solution thereof.
[0041] When the cemented carbide constituting the cutting tool includes the second hard phase, it is expected that various properties of the cutting tool such as heat resistance will be improved.
[0042] [3] The cutting tool preferably has a coating on at least a portion of its surface.
[0043] By providing the coating, the wear resistance of the cutting tool can be further improved, and the life of the cutting tool can be further extended.
[0044] [Details of the embodiments of the present disclosure]
[0045] The following is a description of an embodiment of the present disclosure (hereinafter referred to as "the present embodiment"). However, the following description does not limit the present disclosure. In addition, when a compound or the like is represented by a chemical formula in this specification, its atomic ratio may be any atomic ratio known in the past unless otherwise specified, and is not necessarily limited to an atomic ratio within the stoichiometric range.
[0046] <Cutting tools>
[0047] Reference Figure 1 The cutting tool 1 of the present embodiment is composed of a cemented carbide including a first hard phase and a binder phase. The first hard phase is composed of WC particles. The binder phase contains at least one element selected from Co and Ni.
[0048] The cutting tool 1 includes a main body portion 11 and a surface layer portion 12 provided on the surface of the main body portion 11 .
[0049] On the surface of the flat surface portion of the rake face of the cutting tool 1 , a compressive residual stress of 1.0 GPa or more is applied to the first hard phase 121 .
[0050] The thickness of the surface layer portion 12 is equal to or less than the average grain size of the first hard phase 121 on the surface of the flat surface portion of the rake face.
[0051] The ratio (B / A) of the average grain size (B) of the first hard phase on the surface of the planar portion of the rake face to the average grain size (A) of the first hard phase in the cross section of the body portion is 0.7 or more and less than 1.
[0052] (Main body and surface layer)
[0053] Reference Figure 1 The cutting tool 1 includes a main body portion 11 and a surface layer portion 12 provided on the surface of the main body portion 11 .
[0054] Reference Figure 2 The main body 11 is composed of a binder phase 110 and a first hard phase (WC particles) 111 , etc. The surface layer 12 is also composed of a binder phase 120 and a first hard phase (WC particles) 121 , etc., but the ratio of the binder phase is different from that of the main body 11 .
[0055] The thickness of the surface layer portion 12 is equal to or less than the average grain size of the first hard phase 121 on the surface of the flat surface portion of the rake face.
[0056] The thickness of the surface layer portion 12 can be measured by the following method.
[0057] Using SEM, for example, the magnification is set to 3000 to 5000 times, and the field of view is set to 18μm×25μm, and along a predetermined line extending from the surface side to the inner side of the cutting tool in the thickness direction of the cutting tool, the predetermined cross section of the cutting tool is continuously measured, and the distance in the thickness direction from the surface of the cutting tool to the field of view where the area ratio of the bonding phase is about to first fall below 0.05 is measured. Then, the same measurement is performed at any three positions of the cutting tool, and the average value of the distances obtained by the measurement is set as the thickness of the surface layer portion 12.
[0058] In the present embodiment, a compressive residual stress of 1.0 GPa or more is applied to the first hard phase on the surface of the flat surface portion of the rake face of the cutting tool.
[0059] In addition, the ratio (B / A) of the average grain size (B) of the first hard phase on the surface of the planar portion in the front cutting edge of the cutting tool to the average grain size (A) of the first hard phase in the cross section of the main body of the cutting tool is greater than 0.7 and less than 1. It should be noted that the cross section of the main body is any cross section of the main body 11. For any one cross section of the main body 11, if the average grain size (A) of the first hard phase satisfies the above requirements, the effect of the present disclosure can be obtained. It should be noted that, according to the experiments conducted by the inventors, it can be seen that the selection of the cross section of the main body 11 has no effect on the effect of the present disclosure (the same effect can be obtained even if the cross section of the main body 11 is different).
[0060] In this embodiment, a compressive residual stress of more than 1.0 GPa is imparted to the first hard phase (WC particles) on the surface (front cutting edge) of the cutting tool by sandblasting or the like, while the average particle size of the first hard phase on the surface of the cutting tool is maintained at more than 0.7 times the average particle size of the first hard phase in the interior (main body).
[0061] In the prior art, the application of compressive residual stress by sandblasting or the like is accompanied by the crushing of the first hard phase (WC particles) on the surface (front face), and the average particle size of the first hard phase on the surface is significantly reduced compared to the average particle size of the main body. The reduction in average particle size is synonymous with the increase in surface area. The larger the surface area, the more the area of welding, and the easier it is for the surface (front face) of the cutting tool to react with the cut material. Therefore, damage caused by the reaction between the cutting tool and the cut material, which is a problem in the processing of titanium alloys, is promoted. On the other hand, under sandblasting conditions where the WC particles are not crushed, sufficient compressive residual stress cannot be applied, and damage caused by chipping (notches caused by the shedding of WC particles or the development of cracks generated inside the tool) is easy to occur.
[0062] In contrast, in the present embodiment, sufficient compressive residual stress is imparted to the surface (front cutting edge) of the cutting tool, so that damage caused by cracking at the surface of the cutting tool can be suppressed, and even under sandblasting conditions that can impart sufficient compressive residual stress, the crushing of the first hard phase (WC particles) can be suppressed, thereby suppressing the wear caused by the reaction between the titanium alloy (the material to be cut) and the front cutting edge of the cutting tool, which is accompanied by an increase in the surface area of the cutting tool (front cutting edge) caused by the crushing of the first hard phase.
[0063] Therefore, the cutting tool of this embodiment can extend the life of the cutting tool, especially when used for cutting titanium alloys where damage caused by high reactivity is a problem. The cutting tool of this embodiment is particularly advantageous in a relatively high-speed cutting environment where damage caused by reaction is easy to occur.
[0064] Note that, when compressive residual stress is applied to a cutting tool by sandblasting or the like, the first hard phase (WC particles) in the surface layer portion is crushed, so that B / A is usually less than 1.
[0065] Even when B / A is 0.7 or more, when there is another layer having a composition different from that of the surface layer or the main body, etc., between the surface layer and the main body, etc., the wear resistance of the cutting tool may be reduced due to increased diffusion wear or welding. Therefore, it is preferred that there is no other layer having a composition different from that of the surface layer and the main body, etc., between the surface layer and the main body.
[0066] The average grain size (B) of the first hard phase in the surface of the flat portion of the rake face of the cutting tool is the average grain size of the first hard phase when viewed from a direction perpendicular to the surface of the cutting tool (the normal direction of the surface).
[0067] The average grain size (A) of the first hard phase in the cross section of the main body of the cutting tool is the average grain size of the first hard phase in a plane image (two-dimensional image) when observing from a direction perpendicular to the cross section (the normal direction of the cross section) with respect to any cross section of the cutting tool. Here, the cross section of the main body (a cross section perpendicular to the surface) is a section of the cutting tool excluding the cross section of the surface layer (the range from the surface of the cutting tool to the same depth as the average grain size of the first hard phase in the surface of the flat portion in the rake face).
[0068] In this specification, the average grain size (A and B) of the first hard phase in the above-mentioned surface or cross-section (planar image) is the Heywood diameter calculated by a method using image analysis software described in "<Method for evaluating physical properties of cutting tools>" described later.
[0069] It should be noted that in the present embodiment, the structure of the main body is preferably uniform. When the structure of the main body is uniform, when observing any cross section of the cutting tool by SEM, in the main body, except for the region (surface portion) having an interface with the outside, there is no clearly separable region other than the surface portion.
[0070] (1st hard phase)
[0071] The first hard phase is composed of WC particles.
[0072] The average grain size of the first hard phase in the cross section of the body of the cutting tool is preferably 0.1 μm to 5.0 μm, more preferably 0.5 μm to 3.0 μm. Within this range, a dense cemented carbide having sufficient hardness can be easily obtained.
[0073] (Combination phase)
[0074] The binder phase contains at least one element selected from Co and Ni. It should be noted that the binder phase may further contain other elements within a range in which the effects of the present disclosure are obtained.
[0075] (Second hard phase)
[0076] The cemented carbide preferably further includes a second hard phase. The second hard phase is composed of a compound of at least one element selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table and at least one element selected from the group consisting of C, N, O and B, or a solid solution thereof. By including the second hard phase, oxidation resistance and reaction resistance can be improved, and the effect of suppressing cracks caused by impact on the cutting tool can be imparted to the cutting tool.
[0077] As at least one element selected from the group consisting of elements of Group 4 and Group 5 of the periodic table, for example, titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), and tantalum (Ta) can be cited. As compounds, for example, TiC, NbC, TaC, ZrC, ZrCN, VC, TaNbC, TiN, and TiCN can be cited.
[0078] The average grain size of the second hard phase is preferably 0.1 μm to 3.0 μm, and more preferably 0.2 μm to 0.5 μm. In this case, a dense cemented carbide can be easily obtained.
[0079] Preferably, the first hard phase, the second hard phase and the binding phase are contained in a state where the first hard phase and the second hard phase are dispersed in the binding phase. Thus, the wear resistance of the cutting tool at high temperatures is improved. More preferably, the first hard phase, the second hard phase and the binding phase are contained in a state where they are uniformly dispersed in the cemented carbide. Here, the uniformly dispersed state refers to the presence in the cemented carbide in a state where the first hard phase (and the second hard phase) are in contact with the binding phase and there is less contact between the same phases.
[0080] It should be noted that cemented carbide may also include components other than the above. For example, cemented carbide may include inevitable impurities (B, N, O, etc.) within the scope of not damaging the effect of the present disclosure. In this case, for example, cemented carbide is composed of the first hard phase (or the first hard phase and the second hard phase), a binding phase, and inevitable impurities. In addition, cemented carbide may also include free carbon or an abnormal layer called η phase in its texture.
[0081] The cutting tool according to the present embodiment can be widely used as a cutting tool for various purposes, and can form a smooth cutting surface on the surface of a cut material for a long time. In particular, it can be suitably used as a cutting tool for cutting a cut material including a titanium alloy.
[0082] <Methods for evaluating physical properties of cutting tools>
[0083] The average grain size of the first hard phase on the surface (surface of the flat surface portion of the rake face) and in the cross section of the cutting tool can be determined, for example, by the following method.
[0084] For the surface of the plane portion in the rake face of the cutting tool, or any cross section of the cutting tool obtained using a focused ion beam device, a cross-section polishing device, etc., an SEM (Scanning Electron Microscope) is used to take an image at a magnification of 5000 times from a direction perpendicular to the surface or the cross section, and an electron image of any number of fields of view (for example, 10 fields of view) of 10 or more fields of view is obtained (refer to Figure 5 ). Next, using the attached EPMA (Electron Probe Micro-Analysis) or EDX (Energy Dispersive X-ray Spectrometry), element mapping is performed on a predetermined area (12 μm×9 μm) in each electron image.
[0085] It should be noted that the plane portion in the rake face of the cutting tool referred to here refers to the portion of the concave portion where a chip breaker is not formed in the rake face, and is an arbitrary portion of the area sandwiched by the boundary between the honing area of the front end (the cutting edge ridge connecting the rake face and the back face) and the plane portion, and the virtual line A passing through the point 5 mm away from the boundary in the opposite direction of the above-mentioned front end. It should be noted that the "surface of the plane portion in the rake face of the cutting tool" is the portion of the surface of the surface layer portion 12 of the above-mentioned cutting tool (the surface on the opposite side of the main body portion 11) corresponding to the rake face of the cutting tool.
[0086] Based on the obtained element mapping, particles containing WC are set as the first hard phase, and a phase containing at least one of Co and Ni without containing WC is set as a bonding phase. In addition, particles containing at least one of predetermined Group 4 and Group 5 elements of the periodic table and at least one selected from the group consisting of C, N, O and B without containing WC are set as the second hard phase.
[0087] For this SEM image (element mapping), for example, by performing image analysis using image analysis software ("Mac-View I", manufactured by Mountech Co., Ltd.), the average grain size (Heywood diameter: the average value of the diameter of a virtual circle having the same area as the area of the particles) of the first hard phase on the surface or cross-section of the cutting tool can be calculated.
[0088] First, for each of the first hard phases (WC particles) in the image, the average value of the horizontal Feret diameter and the vertical Feret diameter is obtained. The average particle size of the first hard phase is obtained by adding the average values of the two Feret diameters of each WC particle and dividing it by the number of the first hard phase measured. The number of hard phases in the above-mentioned observation field is preferably more, more preferably more than 100, and more preferably more than 200. It should be noted that the camera magnification can also be changed within the range that does not affect the accuracy of image analysis.
[0089] It should be noted that, through such analysis, the average grain size of the second hard phase can also be measured, and it can also be confirmed in which part of the cutting tool the hard phase (first hard phase and second hard phase) and the binder phase are contained, and the composition of each phase.
[0090] (Determination of compressive residual stress)
[0091] In addition, the compressive residual stress of the first hard phase on the surface of the flat surface of the cutting tool can be measured by, for example, X-ray The measurement conditions are as follows. For example, the average value of the compressive residual stress at any three or more points within 5 mm from the honing position of the rake face of the cutting tool toward the center of the tool is determined.
[0092] (Measurement conditions)
[0093] X-ray output power: 10keV
[0094] X-ray source: radiation
[0095] Measuring surface: (211) surface of the outermost part WC
[0096] Detector: Flat panel
[0097] Spot size: 140nm×230nm
[0098] Scan axis: 2θ / θ
[0099] Scan mode: CONTINUOUS
[0100] <Manufacturing of cutting tools>
[0101] The cutting tool of the present embodiment can be manufactured, for example, by a manufacturing method including a mixing step, a forming step, a sintering step, a cooling step, and a processing step described in detail below. It should be noted that in order to achieve the characteristic structure of the cutting tool of the present embodiment, it is important to control the pressure after the liquid phase appears in the sintering step and the cooling rate in the cooling step.
[0102] (Raw material powder)
[0103] As the raw material powder constituting the binding phase, powder of at least one element selected from Co and Ni is used. In addition, as the raw material powder constituting the hard phase, powders of WC constituting the first hard phase and the compound constituting the second hard phase are used. The Fsss (Fisher Sub-Sieve Sizer) particle size of these powders is preferably 0.5 μm or more and 10 μm or less. It should be noted that the Fsss particle size can be measured by laser diffraction method or the like.
[0104] In the raw material powder constituting cemented carbide, the ratio of WC particles constituting the first hard phase is preferably 70 mass % to 95 mass %, and more preferably 85 mass % to 95 mass %.
[0105] In the raw material powder constituting the cemented carbide, the total ratio of Co and Ni constituting the binder phase is preferably 5 mass % to 15 mass %, more preferably 5 mass % to 10 mass %.
[0106] When the cemented carbide includes the second hard phase, the total proportion of the compounds constituting the second hard phase in the raw material powder constituting the cemented carbide is preferably 0 mass % to 15 mass %, more preferably 0 mass % to 5 mass %.
[0107] In the case where the cemented carbide includes a first hard phase, a binding phase and a second hard phase, in the application of cutting tools for titanium alloys, in order to ensure sufficient hardness and density, it is preferred that, in the raw material composition of the cemented carbide when combined, the proportion of WC constituting the first hard phase is not less than 70 mass % and not more than 95 mass %, the total proportion of Co and Ni constituting the binding phase is not less than 5 mass % and not more than 15 mass %, and the total proportion of compounds constituting the second hard phase is not less than 0 mass % and not more than 15 mass %.
[0108] Furthermore, in order to maintain a good balance between the hardness and toughness of the cemented carbide, it is more preferred that, in the raw material composition of the cemented carbide during compounding, the proportion of WC constituting the first hard phase is greater than 85 mass % and less than 95 mass %, the total proportion of Co and Ni constituting the binding phase is greater than 5 mass % and less than 10 mass %, and the total proportion of the compounds constituting the second hard phase is greater than 0 mass % and less than 5 mass %.
[0109] It should be noted that the composition ratio of the raw material powder is reflected in the composition ratio of the cutting tool finally obtained.
[0110] (Mixing process)
[0111] In the mixing step, the raw material powders are mixed to obtain a mixed powder.
[0112] For mixing, an attritor, a ball mill, a bead mill, a mortar, a jet mill or the like can be used.
[0113] The mixing time is preferably from 0.1 hours to 48 hours, and is more preferably from 2 hours to 15 hours from the viewpoint of uniformly mixing the raw material powders without bias.
[0114] (Forming process)
[0115] In the molding step, the mixed powder obtained in the mixing step is placed in a mold and pressed to obtain a pressed compact (a cutting tool before sintering).
[0116] As the mold, for example, a mold made of cemented carbide (Ta capsule, etc.) can be used. The molding method is not particularly limited as long as it is under general conditions. The pressing pressure is preferably 10 MPa to 16 GPa.
[0117] (Sintering process)
[0118] In the sintering step, the pressed compact obtained in the forming step is sintered.
[0119] The maximum sintering temperature is preferably 1400° C. to 1600° C. The holding time at the maximum temperature is, for example, 0.5 hour to 2 hours. These conditions are not particularly limited as long as they are within the normal range for producing cemented carbide.
[0120] The sintering step is preferably carried out in an inert gas atmosphere such as argon. Regardless of the maximum temperature, it is preferred that the sintering atmosphere be a pressurized atmosphere of 100 kPaG to 400 kPaG from the time when the temperature exceeds 1350°C (after the liquid phase appears).
[0121] (Cooling process)
[0122] In the cooling step, the sintered body (cutting tool) is cooled after the sintering is completed.
[0123] In the cooling step, the time taken to reduce the temperature of the cutting tool from the maximum temperature to 1300° C. is preferably 0.2 hours to 1 hour. The cooling rate in the region below 1300° C. is not particularly limited.
[0124] The cooling process is preferably carried out in an inert gas atmosphere such as argon. In addition, the partial pressure of the atmosphere gas in the cooling process is preferably 400 kPaG or more, more preferably 400 kPaG or more and 650 kPaG or less. In particular, by carrying out cooling from the highest temperature in a pressurized atmosphere of 400 kPaG or more, cooling can be carried out at a sufficient cooling rate.
[0125] (Processing steps)
[0126] In the machining process, a treatment is performed to impart a compressive residual stress of 1.0 GPa or more to the surface (rake face) of the cutting tool. It should be noted that the treatment to impart a compressive residual stress of 1.0 GPa or more can also serve as a honing treatment of the front end of the cutting tool.
[0127] Examples of the treatment for imparting compressive residual stress include sandblasting, etc. Examples of the sandblasting include wet sandblasting, etc.
[0128] Examples of materials for the medium (object projected onto the tool) used in blasting such as wet blasting include nonmetals such as alumina, steel, etc. It should be noted that a sphere is often used as the medium, but it does not necessarily have to be a true sphere.
[0129] The conditions for the sandblasting treatment are not particularly limited as long as they are conditions that can impart a compressive residual stress of 1.0 GPa or more (preferably 1.0 GPa or more and 2 GPa or less). In the case of imparting a compressive residual stress of 1.0 GPa or more by wet sandblasting, for example, the linear distance between the projection port of the medium and the surface (front face) of the cutting tool is 80 mm or more and 120 mm or less, the pressure applied to the medium (also referred to as projection pressure) is 0.1 MPa or more and 0.3 MPa or less, the projection time is 10 seconds or more and 45 seconds or less, the projection angle relative to the normal line of the front face is 30° or more and 90° or less, and the diameter of the medium is 0.1 mm or more and 1.0 mm or less.
[0130] (principle)
[0131] Hereinafter, the principle of realizing the characteristic structure of the cutting tool of the present embodiment by the above-mentioned manufacturing method will be described.
[0132] Generally, when sintering cemented carbide, the bonding phase elements (Co, Ni) become liquid phase at about 1320°C (depending on the carbon content), and the alloy is densified. However, at this time, the liquid phase moves due to the temperature difference between the inside and the surface of the alloy or the atmosphere. As a result, the amount of bonding phase on the surface and inside and the particle size of the hard phase change. Therefore, in this embodiment, a predetermined pressurized atmosphere is formed at a temperature above the liquid phase appearance temperature (about 1320°C) in the sintering process to control the bonding phase amount of the surface layer of the cutting tool.
[0133] It should be noted that in many prior arts, in addition to promoting the densification of the alloy, the atmospheric gas is not pressurized but depressurized in order to form a layer with a certain function. However, in such a depressurized atmosphere, the binding phase elements and carbon are easily volatilized from the surface of the cutting tool, so that the amount of binding phase on the surface of the cutting tool is relatively small.
[0134] On the other hand, when an excessive pressure is applied under pressure, elemental diffusion of the liquid phase and carbon to the surface and movement due to the flow of the liquid phase are hindered, thereby reducing the amount of the bonding phase on the surface of the cutting tool.
[0135] Thus, when the amount of bonding phase on the surface of the cutting tool is small, the retention force of the WC particles is insufficient during the treatment of applying compressive stress such as sandblasting, and the particles are easily broken and fall off. In this case, the surface area of the cutting tool is relatively increased, which promotes the wear caused by the reaction between the titanium alloy (cutting material) and the cutting tool.
[0136] In contrast, in the present embodiment, a predetermined pressurized atmosphere is formed at a temperature above the liquid phase appearance temperature in the sintering process, thereby controlling the amount of the bonding phase on the surface of the cutting tool to an appropriate amount. As a result, when a treatment such as sandblasting is performed to impart compressive stress, the crushing and shedding of WC particles on the surface of the cutting tool can be suppressed, and the surface area of the cutting tool becomes relatively small. Therefore, the wear caused by the reaction between the titanium alloy (the material to be cut) and the cutting tool can be suppressed.
[0137] In addition, in the present embodiment, in the cooling process, by rapidly cooling in a pressurized atmosphere, the size of the WC particles on the surface of the cutting tool can be made uniform and close to a spherical shape. As a result, the surface area of the cutting tool becomes relatively small. Therefore, the wear caused by the reaction between the titanium alloy (the material to be cut) and the cutting tool can be suppressed.
[0138] It should be noted that, in the cooling in the temperature region where the liquid phase appears, when the cooling rate is slow (e.g., 10°C / min), the particle growth of the WC particles is promoted, and the size (particle diameter) of the WC particles on the surface of the cutting tool becomes uneven, and the shape becomes a square shape. The inventors have found that in the surface portion where there are many WC particles whose particle growth is promoted, the WC particles are easily broken when the treatment of applying compressive residual stress such as sandblasting is performed, and that the breakage of the WC particles can be suppressed by cooling at a relatively fast speed so that the particle growth of the WC particles does not proceed.
[0139] As described above, by controlling the pressure in the firing process and the cooling rate in the cooling process, the surface area of the cutting tool of this embodiment becomes relatively small, thereby suppressing the wear of the cutting tool caused by the reaction between the titanium alloy (the workpiece) and the cutting tool.
[0140] It should be noted that examples of cutting tools include drills, end mills, cutting blade indexable cutting inserts for drills, cutting blade indexable cutting inserts for end mills, cutting blade indexable cutting inserts for milling, cutting blade indexable cutting inserts for turning, metal saws, gear cutting tools, reamers, taps, etc.
[0141] (Laminating)
[0142] In addition, the cutting tool may also have a coating on at least a portion of the surface. By having the coating, the wear resistance of the cutting tool can be further improved, and the life of the cutting tool can be further extended. In addition, the characteristics of the coating can also be given to the cutting tool.
[0143] As the coating, it is preferred to use a 7×10 -6 / K above 9×10 -6 The coating has a thermal expansion coefficient of 0.1 / K or less. The coating composition is preferably a nitride or carbonitride of one or more elements selected from the group consisting of Ti, Al, Cr, Si, Hf, Zr, Mo, Nb, Ta, V, and W.
[0144] In addition, the coating preferably has an oxidation resistance of 1000° C. or higher. Here, “having an oxidation resistance of 1000° C. or higher” means that the coating is evaluated in the atmosphere by a thermal analysis-differential thermal / thermogravimetry (TG / DTA: Thermogravimetry / Differential Thermal Analysis) device, and the temperature at which the weight increase occurs is 1000° C. or higher. Preferred examples of the composition constituting the coating having such oxidation resistance include AlTiSiN, AlCrN, TiZrSiN, CrTaN, HfWSiN, CrAlN, and the like.
[0145] Such a film can be formed by any method of physical vapor deposition (PVD) method and chemical vapor deposition (CVD) method. When the film is formed by the CVD method, it is easy to obtain a film with excellent adhesion to the cemented carbide (cutting tool). As the CVD method, for example, a thermal CVD method can be cited. When the film is formed by the PVD method, compressive residual stress can be given, and its toughness can be easily improved. From the aspect that the adhesion of the film and the cemented carbide (cutting tool) is significantly improved, the cathode arc ion plating method can also be used.
[0146] The coating in the cutting tool of the present embodiment is preferably coated on the portion of the cutting edge of the cutting tool and its vicinity, or may be coated on the entire surface of the cutting tool. In addition, the coating may be a single layer or a multilayer. The thickness of the coating is preferably 1 μm to 20 μm, more preferably 1.5 μm to 15 μm.
[0147] Example
[0148] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.
[0149] <Examples 1 to 13 and Comparative Examples 101 to 108>
[0150] First, using a variety of compound powders and metal powders represented by the combination composition (WC, NbC, TaC, Co and Ni) described in Table 1 as raw material powders, throwaway chips (cutting tools) of CNMG 432 shape (manufactured by Sumitomo Electric Hardmetal Co., Ltd.) composed of the cemented carbides involved in Examples 1 to 13 and Comparative Examples 101 to 108 were produced in the same manner as the manufacturing method of the cutting tool described in the above embodiment.
[0151] It should be noted that, in the mixing process, a grinding mill was used for mixing for 12 hours. In addition, the pressing pressure of the forming process was set to 100 MPa. The maximum temperature in the sintering process was set to 1450°C, and the holding time of the maximum temperature was set to 1 hour. The atmosphere gas in the cooling process was argon, and the partial pressure of the atmosphere gas was set to 400 kPaG. The atmosphere pressure in the sintering process and the cooling time (the time from the maximum temperature to 1300°C) of the cooling process were set as shown in Table 1.
[0152] In addition, in the processing step (a process of imparting a compressive residual stress of 1.0 GPa or more to the front cutting edge of the cutting tool by wet sandblasting), the linear distance between the projection port of the medium and the surface (front cutting edge) of the cutting tool is 100 mm, the pressure (projection pressure) applied to the medium is 0.2 MPa, the projection time is 30 seconds, the projection angle relative to the normal of the front cutting edge is 45°, and the diameter of the medium (aluminum oxide sphere) is 1.0 mm. However, in Example 2, the projection time is 20 seconds, and in Comparative Example 102, the projection time is 10 seconds. In addition, only in Example 4, under the conditions of the above-mentioned processing step (sandblasting), a compressive residual stress of 1.0 GPa is imparted to the front cutting edge of the cutting tool by setting the projection pressure to 0.10 MPa.
[0153] For the cutting tools of the obtained examples and comparative examples, the average grain size (A) of the first hard phase in the cross section of the main body and the average grain size (B) of the first hard phase on the surface of the planar portion in the rake face were measured by the method described in the above embodiment. In addition, the ratio (B / A) of the average grain size (B) of the first hard phase on the surface of the planar portion in the rake face to the average grain size (A) of the first hard phase in the cross section of the main body was calculated. These measurement results are shown in Table 1.
[0154] in addition, Figure 6 is a SEM photograph of the surface of the cutting tool of Example 1 (the surface of the flat surface portion in the rake face), Figure 7 : are SEM photographs of the surface of the cutting tool of Comparative Example 101. From these photographs, it can be seen that in Example 1, the crushing of the first hard phase on the surface of the cutting tool due to the processing step is less than that in Comparative Example 101.
[0155] It should be noted that, for the cutting tools of each embodiment and comparative example, the thickness of the surface portion is measured by the method described in the above embodiment. According to the measurement results, in embodiments 1 to 13 and comparative examples 101 to 107, the thickness of the surface portion is less than the average particle size of the first hard phase (WC particles) in the surface of the planar portion in the front cutting edge of the cutting tool. On the other hand, in comparative example 108, the thickness of the surface portion is greater than the average particle size of the first hard phase (WC particles) in the surface of the planar portion in the front cutting edge of the cutting tool. It should be noted that, in comparative example 108, the surface portion is relatively thicker due to the relatively long cooling time. The results of measuring the average particle sizes of the first hard phase and the second hard phase by the method described in the above embodiment are shown in Table 1.
[0156] <Abrasion resistance evaluation>
[0157] The following wear resistance evaluation was performed on the throwaway inserts (cutting tools) obtained in the above-mentioned respective Examples and Comparative Examples.
[0158] For each cutting tool, in a high-load cutting test (wear resistance test) under the following cutting conditions, the cutting time until the wear amount of the back face of the cutting edge of the cutting tool reaches 0.2 mm was measured. The results of the cutting time measurement are shown in Table 1. It should be noted that the cutting time shown in Table 1 is the average value of the four corners of each cutting tool. The longer the cutting time, the better the wear resistance.
[0159] (Cutting conditions)
[0160] Cutting material: Ti alloy (Ti-6Al-4V)
[0161] Cutting speed (Vc): 100m / min
[0162] Cutting depth (ap): 2.0mm
[0163] Feed rate (f): 0.1mm / rev
[0164] Cutting environment: WET (wet)
[0165] [Table 1]
[0166]
[0167] From the results shown in Table 1, it can be seen that in Examples 1 to 13 that all meet the requirements of the cutting tool of the present disclosure, the cutting time is long and the wear resistance is excellent, compared with the comparative examples that do not meet the requirements of the cutting tool of the present disclosure.
[0168] It should be noted that, from the results of Comparative Example 102, it can be seen that, as in the prior art, when only the sandblasting conditions are weakened in order to suppress the breakage of WC, although the value of B / A meets the requirements of the present disclosure, the cutting time will not be extended because a compressive residual stress of more than 1.0 GPa that meets the requirements of the present disclosure is not given.
[0169] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present disclosure is indicated by the claims rather than the embodiments described above, and is intended to include all changes within the meaning and scope equivalent to the claims.
[0170] Explanation of symbols
[0171] 1 cutting tool, 11 main body, 110 bonding phase of the main body, 111 first hard phase of the main body, 12, 14 surface layer, 120 bonding phase of the surface layer, 121 first hard phase of the surface layer, 13 surface layer
Claims
1. A cutting tool comprising a cemented carbide comprising a first hard phase and a binder phase, The first hard phase is composed of WC particles, The bonding phase contains at least one element selected from Co and Ni, The cutting tool comprises a main body portion and a surface layer portion provided on a surface of the main body portion. A compressive residual stress of 1.0 GPa or more is applied to the first hard phase on the surface of the flat surface portion of the rake face of the cutting tool, The thickness of the surface layer portion is equal to or less than the average grain size of the first hard phase on the surface of the flat surface portion of the rake face. a ratio of a second average grain size of the first hard phase on the surface of the flat surface portion of the rake face to a first average grain size of the first hard phase on the cross section of the main body portion of 0.7 or more and less than 1, The second average grain size is an average grain size of the first hard phase in a planar image when the surface of the planar portion of the rake face of the cutting tool is observed from a direction perpendicular to the surface of the planar portion. The first average grain size is the average grain size of the first hard phase in a planar image when observed from a direction perpendicular to the cross-section of the main body relative to the cross-section of the main body, and the cross-section of the main body is the portion of any cross-section of the cutting tool excluding the cross-section of the surface layer portion.
2. The cutting tool according to claim 1, wherein: The cemented carbide further comprises a second hard phase, The second hard phase is composed of a compound of at least one element selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table and at least one element selected from the group consisting of C, N, O and B, or a solid solution thereof.
3. The cutting tool according to claim 1, wherein: The main body and the surface layer further include a second hard phase, The second hard phase is composed of a compound of at least one element selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table and at least one element selected from the group consisting of C, N, O and B, or a solid solution thereof.
4. The cutting tool according to claim 2 or 3, wherein: The second hard phase has a composition different from that of the first hard phase.
5. The cutting tool according to claim 1, wherein: The ratio of the second average particle size to the first average particle size is 0.73 or more and less than 1.
6. The cutting tool according to claim 1, wherein: The first average particle size is not less than 0.1 μm and not more than 5.0 μm.
7. The cutting tool according to claim 2 or 3, wherein: The first hard phase and the second hard phase are dispersed in the binder phase.
8. The cutting tool according to claim 1 or claim 2, wherein: A coating is provided on at least a portion of the surface of the cutting tool.
Citation Information
Patent Citations
Cemented carbide cutting tool insert for turning processing titanium alloy
JP2003001505A
Method for manufacturing laminate and method for manufacturing semiconductor device
JP2020091490A
Cermet, cutting tool, and method for manufacturing cermet
CN106232846A
Die made from sintered hard metal alloy
JP2003113438A